Analisis Good Corporate Governance Dalam Perspektif Islam Terhadap Transaksi Jual Beli Secara Online Pada Aplikasi Shopee - Machfudyah, Arida Dwi; Ayuni, Lisa; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
This study aims to analyze corporate governance in an Islamic perspective on buying and selling transactions online on the shopee application. The data sources used by the authors were obtained from interviews with various informants from research subjects and secondary data in the form of written notes on the results of the interviews conducted. The way this research works is aimed at knowing gcg analysis in an Islamic perspective on buying and selling transactions online on the shopee application.